Funcionalização do Peuamm com anidrido maleico via moagem de alta energia - Mathias, Ivan (2010)
In this work the ultra high molecular weight polyethylene grafting with maleic anhydride by ball milling process was studied. UHMWPE with molecular weight of 8x106 g.mol-1, maleic anhydride and benzoyl peroxide were used. The ball milling process was performed in Attritor and Spex mills. The milling time, peroxide concentration and, in case of Attritor mill, the rotation, were the variables studied. We used two distinct levels for each variable and all possible combinations were studied with the use of statistical analysis for better interpretation of the results. The residual maleic anhydride was extracted from the samples by soxhlet extractor with acetone as a solvent. FTIR, SEM, XRD and bulk density measurements were performed for characterization. FTIR results revealed that the UHMWPE graft with maleic anhydride occurred for the processing in both mills. In case of the Attritor mill, the milling time and the rotation were the most influent variables in UHMWPE grafting. The peroxide concentration also affected the process, but with less intensity. For the Spex mill processing, the milling time was the most influent variable in grafting process, with the peroxide concentration again affecting less the process. The ball milling modified the polymer particles morphology, transforming from sphere to flake like. This transformation occurred in different levels, being correlated with milling time and rotation in case of Attritor mill. According to the change in the shape of the polymer particles, the bulk density was also affected by the same variables. The polymer crystalline structure was studied by XRD, where the influence on the variables was determined for the formation of monoclinic and orthorhombic phases. It was found that for the Attritor mill, the milling process induces the formation of a monoclinic phase, but it proved independent of the variables involved in the ball milling process. To the Spex mill processing, no change was detected in the concentration of the monoclinic phase, probably due to the warming occurred in the process that promotes the monoclinic-orthorhombic inversion around 70 º C. The ball milling also affected the thermal properties of the polymer, such as temperature and enthalpy of melting and crystallization. In this case, any variable proved influential in differentiating these thermal properties of milled samples in different conditions. The only significant difference was observed between the thermal properties of the milled samples for the no milled sample.